APPLICATION OF TOLERANCE VALUES AND SOCIAL ATTITUDES IN SOCIETIES OF DIFFERENT RELIGION IN DUSUN BONDALEM DESA JUMO KECAMATAN JUMO TEMANGGUNG DISTRICT - Elok Ivada Maisara (Afeksi: Jurnal Penelitian dan Evaluasi Pendidikan, 2021)
The purpose of this study was to determine the application of the values of tolerance for people of different religions, the application of social attitudes to people of different religions as well as the driving and inhibiting factors for the application of the values of tolerance and social attitudes of interfaith communities in Dusun Bondalem, Jumo Village, Jumo District. Temanggung Regency. This study uses a qualitative research approach because the data and research results obtained are processed and explained based on the author's description. Sources of data in the study include primary data sources, namely the results of interviews, and secondary data sources which can be photos of activities in the community. The results showed that the application of the values of tolerance and social attitudes of the people of different religions in Bondalem Hamlet was the presence of every activity of the people of the Bondalem Hamlet community, all residents participated regardless of their religious background. This is manifested in the daily attitudes of residents in Bondalem Hamlet. The social attitudes that exist in the people of Bondalem Hamlet are very good and are well implemented by the residents of Bondalem Hamlet. The driving factor: all residents want a safe, peaceful and prosperous life, so that in this Bondalem Hamlet, all residents mingle to create such community life. The inhibiting factors for community members in Bondalem Hamlet are economic problems that are generally middle to lower, as well as social problems where residents are fanatical about their religion and problems arise.